Proceedings of the 2nd International Conference on Social, Applied Science, and Technology in Home Economics (ICONHOMECS 2019) 2020
DOI: 10.2991/assehr.k.200218.018
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Leaves Flour and Tengger Potato Flour as Composite Flour for GFCF Diets

Abstract: Composite flour ratio Tengger potato starch and flour made with the aim of Moringa leaves as a substitute for wheat flour containing gluten and casein to be used as raw material products GFCF (Gluten Free Casein Free). The experimental design use completely randomized design consisted of four treatments (ratio of Tengger's potato starch and moringa leaf powder 100%: 0%, 96%: 4%, 95%: 5% and 94%: 6%) and three replications; and then analyzed to determine the proximate contents (water, ash, protein, fat, crude f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…M. olifera seeds 38 or leaves 39 were utilized as a fortifying ingredient of the biscuit. Indeed, Kiranawati et al 40 used a composite flour of potato starch and Moringa leaves flour to substitute wheat to produce GF and casein-free staple foods (cookies and snacks). These authors revealed that the best composite flour with similar properties to wheat flour is composed of a ratio potato starch/Moringa leaves flour of 94% / 6%.…”
Section: Moringa Flourmentioning
confidence: 99%
See 1 more Smart Citation
“…M. olifera seeds 38 or leaves 39 were utilized as a fortifying ingredient of the biscuit. Indeed, Kiranawati et al 40 used a composite flour of potato starch and Moringa leaves flour to substitute wheat to produce GF and casein-free staple foods (cookies and snacks). These authors revealed that the best composite flour with similar properties to wheat flour is composed of a ratio potato starch/Moringa leaves flour of 94% / 6%.…”
Section: Moringa Flourmentioning
confidence: 99%
“…They concluded that only breads with 20 g/100 g of enrichment showed a significant increase in total, soluble and insoluble fibers. While Oniszczuk et al 59 mixed different amounts of chestnut flour (10,20,30,40, and 50%) with rice and bean flours to produce innovative GF pasta. In a sample containing 20% or more of chestnut flour, up to 13 amino acids were detected.…”
Section: Novel Ingredients In Gluten-free Cereal Productsmentioning
confidence: 99%